China's Evolving Policy Towards the Chinese Diaspora in Southeast Asia (1949-2018) - An, Wu Xiao (ISEAS - Yusof Ishak Institute, 2019)
The Chinese diaspora, consisting of both Chinese living overseas who are citizens of China (huaqiao), and people of Chinese descent who are citizens of foreign countries (huaren), have significantly shaped the making of modern China. China's policy towards its diaspora is primarily governed by its national interests and foreign policy imperatives. However, the Chinese government has been careful to ensure that the huaqiao and the huaren fall into different policy domains: Chinese citizens living overseas are subject to China's domestic policies, while Chinese descendants who are citizens of oth.